2014
DOI: 10.1111/mmi.12711
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar biosynthesis exerts temporal regulation of secretion of specific Campylobacter jejuni colonization and virulence determinants

Abstract: Summary The Campylobacter jejuni flagellum exports both proteins that form the flagellar organelle for swimming motility and colonization and virulence factors that promote commensal colonization of the avian intestinal tract or invasion of human intestinal cells, respectively. We explored how the C. jejuni flagellum is a versatile secretory organelle by examining molecular determinants that allow colonization and virulence factors to exploit the flagellum for their own secretion. Flagellar biogenesis was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 85 publications
5
52
0
Order By: Relevance
“…The presence of flagella on C. jejuni 81116 and derivative mutant strains was examined similarly to a previously described method19. Briefly, the strains were grown on MH agar, containing appropriate antibiotics, at 37 °C under microaerophilic conditions for 48 h. A 100 μl aliquot of water was used to suspend the cells, and the cells were gently scraped from the surface of the plate using a sterile plastic inoculating loop.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of flagella on C. jejuni 81116 and derivative mutant strains was examined similarly to a previously described method19. Briefly, the strains were grown on MH agar, containing appropriate antibiotics, at 37 °C under microaerophilic conditions for 48 h. A 100 μl aliquot of water was used to suspend the cells, and the cells were gently scraped from the surface of the plate using a sterile plastic inoculating loop.…”
Section: Methodsmentioning
confidence: 99%
“…The cells of the food-borne pathogen, Campylobacter jejuni ( C. jejuni ) are spiral-shaped and are able to move using unipolar or bipolar flagella, in comparison with rod-shaped S. enterica cells, which move using many peritrichous flagella over the cell surface1617. Uniquely, the C. jejuni flagellar hook is also used to export virulence factors during colonization of the avian or human host1819. Intriguingly, the C. jejuni hook protein, FlgEcj, has one of the longest amino acid sequences compared with other bacterial FlgE proteins20.…”
mentioning
confidence: 99%
“…For SILAC labelled cultures, once isotopic amino acid incorporation was achieved a previously published protocol for the generation of C. jejuni supernatants [6], [12] was utilised, adapted here for use with DMEM. Bacteria were suspended to an OD 600nm of 0.6 in 20mls SILAC DMEM (Thermo Fisher Scientific) supplemented with a relevant amount of “light” (wild type samples) or “heavy” (mutant samples) l -Arginine, and 10 mM l -Glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified multiple components of the C. jejuni flagellum that are required for the export of the Campylobacter invasion antigens (Cia), and other non-flagellar proteins, some of which have been implicated in the ability of C. jejuni to invade human intestinal cell lines [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17]. CiaB was the first non-flagellar C. jejuni protein proposed to be dependent upon the flagellum for secretion, and is required for efficient invasion of INT-407 cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…The C. jejuni fl agellum also serves as a type-III secretion system for the extracellular release of factors that may control bacteria-host interactions [12][13][14][15]. These secreted effector proteins include the so-called Campylobacter invasion antigens (CiaA-H) and fl agellar coexpressed determinants (FedA-D) [13,[16][17][18]. Moreover, C. jejuni binding to host target cells has been reported to include a series of outer membrane adhesins such as PEB1, MOMP, JlpA, CadF, and FlpA [10,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%